Diet of Ameerega braccata (Steindachner, 1864) (Anura: Dendrobatidae) from Chapada dos Guimarães and Cuiabá, Mato Grosso State, Brazil - LR. Forti; ASO. Tissiani; T. Mott; C Strüssmann (Brazilian Journal of Biology)
The understanding of feeding habits is important for anurans in general, both from an ecological and a phylogenetic perspective. For diurnal poison frogs belonging to the Dendrobatidae family, diet aspects play a crucial role in their defense and survival. Herein, we investigated feeding habits, foraging behaviour, and overall effects of habitat, sex, and body size on the diet of individuals of Ameerega braccata, a poorly known dendrobatid species. Specimens were observed and collected in the type-locality, Chapada dos Guimarães, and in the neighbouring municipality of Cuiabá, both in the State of Mato Grosso, Midwestern Brazil. The most important prey categories for A. braccata were Formicidae, Isoptera, and Acari, whose representatives were caught during active foraging. Individuals from Chapada dos Guimarães population consumed more Acari but fewer Isoptera than individuals from Cuiabá. Despite this, niche breadth values were narrow and similar for the two populations. Individuals from two distinct habitats (campo sujo and cerrado stricto sensu) showed differences in their diet, probably as an effect of differential prey availability. Females consumed more Isoptera than males. The number of prey categories used as food was not influenced by the variation of body size of the target species. However, the abundance and the volume of consumed Acari were statistically correlated with body size. The main results suggest that Ameerega braccata has a narrow niche breadth, as well as a specialised diet in ants, termites, and mites, which reinforces the hypotheses of close association between Acari consumption and the presence of skin toxic alkaloids, already found in other species of Dendrobatidae. Although differences in prey consumption between sexes are uncommon among poisonous frogs, differences in the diet composition between age classes, which probably reduce intraspecific competition, are frequently reported.